Upgrading the beam telescopes at the DESY II Test Beam Facility - Augustin, Heiko; Diener, R.; Dittmeier, Sebastian; Freeman, P. M.; Hammerich, J.; Herkert, A.; Huth, K.; Immig, David; Krämer, U.; Meyners, N.; Perić, I.; Schäfer, O.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2022)
The DESY II Test Beam Facility is a key infrastructure for modern high energy physics detector development, providing particles with a small momentum spread in a range from 1 to 6 GeV to user groups e.g. from the LHC experiments and Belle II as well as generic detector R&D. Beam telescopes are provided in all three test beam areas as precise tracking reference without time stamping, with triggered readout and a readout time of 115 s . If the highest available rates are used, multiple particles are traversing the telescopes within one readout frame, thus creating ambiguities that cannot be resolved without additional timing layers. Several upgrades are currently investigated and tested: Firstly, a fast monolithic pixel sensor, the TelePix, to provide precise track timing and triggering on a region of interest is proposed to overcome this limitation. The TelePix is a 180 nm HV-CMOS sensor that has been developed jointly by DESY, KIT and the University of Heidelberg and designed at KIT. In this publication, the performance evaluation is presented: The difference between two amplifier designs is evaluated. A high hit detection efficiency of above 99.9 % combined with a time resolution of below 4 ns at negligible pixel noise rates is determined. Finally, the digital hit output to provide region of interest triggering is evaluated and shows a short absolute delay with respect to a traditional trigger scintillator as well as an excellent time resolution. Secondly, a fast LGAD plane has been proposed to provide a time resolution of a few 10 ps, which is foreseen to drastically improve the timing performance of the telescope. Time resolutions of below 70 ps have been determined in collaboration with the University of California, Santa Barbara.
Gesehen am 06.04.2023